2019
DOI: 10.3390/molecules24112068
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution and Anti-Lung Cancer Effect of 10-Hydroxycamptothecin Combined with Platycodonis Radix and Glycyrrhizae Radix ET Rhizoma

Abstract: 10-Hydroxycamptothecin (HCPT) is a broad-spectrum chemotherapeutic drug, although its side effects and multidrug resistance (MDR) limit its clinical application. A range of drug delivery systems have been utilized to overcome its shortcomings and maintain its therapeutic efficacy, however the use of the transport effect of traditional Chinese medicines (TCMs) to improve the distribution of chemotherapeutic drugs has not been widely reported. Platycodonis Radix (JG) and Glycyrrhizae Radix ET Rhizoma (GC) are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…TCM can act on multiple components of interest at once, which is likely key to reversing MDR. 14 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCM can act on multiple components of interest at once, which is likely key to reversing MDR. 14 17 …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, combining traditional Chinese medicine (TCM) with chemotherapeutic drugs to combat MDR has been proposed. TCM can act on multiple components of interest at once, which is likely key to reversing MDR. …”
Section: Introductionmentioning
confidence: 99%
“…This finding may partially explain why HSYW decrease the incidence rate of the side effects of this anticancer agent, owing to the highest plasma exposure is always tightly linked to the frequency of the side effects of therapeutic drugs, especially for those drugs with a narrow therapeutic window. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%
“…Four ingredients of T33, specifically Gansui (Kansui Radix), Zhigancao (Glycyrrhizae Radix et Rhizoma Praeparata cum Melle), Baishao (Paeoniae Radix Alba), and Jiangbanxia (Pinelliae Rhizoma Praeparatum Cum Zingibere et Alumine), are known as Gan Sui Ban Xia Tang, which has long been used in the treatment of spontaneous diarrhea and malignant pleural effusion 16,17 . Much evidence has also indicated that each component of T33 has been used in treatments for various cancers 15,18–26 . However, information about the effects of T33 on colon cancer is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…16 , 17 Much evidence has also indicated that each component of T33 has been used in treatments for various cancers. 15 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 However, information about the effects of T33 on colon cancer is still limited.…”
Section: Introductionmentioning
confidence: 99%